Comics, Da'wa, and the Representation of Religious Moderation - Zulhazmi, Abraham Zakky (DINIKA : Academic Journal of Islamic Studies, 2022)
This study aims to show the representation of religious moderation which is generated in three comic books on the topic of hijrah, a term now connoting a change in behavior from negative behaviors to good ones in relation to obedience to the rules of Islam. The choice of the topic was dictated by the fact that hijrah has been on a growing trend among middle-class Muslims in past years. This is literature research using interpretive method of qualitative research. The theory used in this research was Stuart Hall’s theory of representation. Hall stated that meanings are determined by language. In this study, the researcher tried to convey the meanings attached to pictures and dialogues in three comic books under study to show the representation of religious moderation. This research came to a conclusion that the three comic books on the topic of hijrah (Black Metal Istiqomah by Achmad Deptian, Hijrah; Saatnya Berubah by Dzulhilman Roslan and Megat Mohd Faris and iQomic volume 2: Hijrah in an anthology compiled by 14 comic-book writers) demonstrate and the value of religious moderation. Anti-violence, tolerance, and acceptance of local cultures are often taken as the indicators of religious moderation. Those indicators can be seen from the narration (dialogues and plots) developed and visual images produced in those comic books.